Emerging trends in olive oil fraud and possible countermeasures. (June 2021) - Casadei, Enrico; Valli, Enrico; Panni, Filippo; Donarski, James; Farrús Gubern, Jordina; Lucci, Paolo; Conte, Lanfranco; Lacoste, Florence; Maquet, Alain; Brereton, Paul; Bendini, Alessandra; Gallina Toschi, Tullia
Abstract: A review of most common types of fraud in the olive oil sector has been carried out. The work was supplemented by the results of an international on-line survey of EU and non-EU stakeholders in the olive oil sector. The review confirms that most common infringements (fraud or non-compliance) are the marketing of virgin olive oil as extra virgin, and blends of other vegetable oils (sunflower, corn, palm, rapeseed, etc.) with olive oil being marketing as olive oil. The on-line survey focused on current and future issues facing a range of stakeholders, e.g. exporters, importers, control laboratories. Of seemingly high priority to industry were emerging issues with regards to fraud arising from the addition of deodorized oil and from mixing with oil obtained by a second centrifugation of the olive paste ( remolido ). On the same line, a questionnaire, addressed to the EU Food Fraud Network National Contact Points, highlighted that the most frequent fraudulent practice is mixing with lower quality olive oils and that EU, non-EU and mix of EU and non-EU oils are the cases which need more control activities in relation to false designations of origin. Highlights: EU FFN 2019 annual report placed olive oil as a vulnerable food product for fraud. Results of an on-line survey to EU and non-EU stakeholders are showed. A questionnaire addressed to the EU FFN National Contact Points is presented. A priority is to fight illegal mix with deodorized, remolido or lampante olive oils. Most frequent fraud related to mixed olive oils is with lower quality products.